The effects of transformational leadership and motivation on teacher performance at yayasan rabiatul adawiyah medan - Sinaga, Ira; Hidayat, Ferry; Hoki, Leony (Central Research Institute for Agriculture (CeRIA), 2024)
This study aims to determine the effect of transformational leadership and motivation on the performance of teachers in Yayasan Rabiatul Adawiyah Medan. Data collection techniques involved the distribution of questionnaires to a sample of 35 people. The data analysis model used was multiple linear regression. The coefficient of determination (r2) was obtained at 72.8%, indicating that the independent variables of transformational leadership and motivation can explain their effect on teacher performance by 72.8%, while the rest of the variables are not revealed. The results of the study, at a 95% confidence level and a 5% significance level, showed that leadership has a significant effect on teacher performance, and motivation has a significant effect on employee performance. Simultaneously, it is known that transformational leadership and motivation together have a significant effect on teacher performance. Transformational leadership carried out by the principal should also involve consideration of the opinions or suggestions of teachers when making decisions and giving certain appreciation when teachers achieve an accomplishment. The role of teachers as the main pillar in the world of education can be a source of pride if the work done is appreciated